Mechanism of resistance to mesotrione in an Amaranthus tuberculatus population from Nebraska, USA. - Shiv S Kaundun; Sarah-Jane Hutchings; Richard P Dale; Anushka Howell; James A Morris; Vance C Kramer; Vinod K Shivrain; Eddie Mcindoe (PLoS ONE)
Amaranthus tuberculatus is a troublesome weed in corn and soybean production systems in Midwestern USA, due in part to its ability to evolve multiple resistance to key herbicides including 4-hydroxyphenylpyruvate dioxygenase (HPPD). Here we have investigated the mechanism of resistance to mesotrione, an important chemical for managing broadleaf weeds in corn, in a multiple herbicide resistant population (NEB) from Nebraska. NEB showed a 2.4-fold and 45-fold resistance increase to mesotrione compared to a standard sensitive population (SEN) in pre-emergence and post-emergence dose-response pot tests, respectively. Sequencing of the whole HPPD gene from 12 each of sensitive and resistant plants did not detect any target-site mutations that could be associated with post-emergence resistance to mesotrione in NEB. Resistance was not due to HPPD gene duplication or over-expression before or after herbicide treatment, as revealed by qPCR. Additionally, no difference in mesotrione uptake was detected between NEB and SEN. In contrast, higher levels of mesotrione metabolism via 4-hydroxylation of the dione ring were observed in NEB compared to the sensitive population. Overall, the NEB population was characterised by lower levels of parent mesotrione exported to other parts of the plant, either as a consequence of metabolism in the treated leaves and/or impaired translocation of the herbicide. This study demonstrates another case of non-target-site based resistance to an important class of herbicides in an A. tuberculatus population. The knowledge generated here will help design strategies for managing multiple herbicide resistance in this problematic weed species.